2021
DOI: 10.1016/j.apsb.2021.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine in COVID-19

Abstract: COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread across the globe, posing an enormous threat to public health and safety. Traditional Chinese medicine (TCM), in combination with Western medicine (WM), has made important and lasting contributions in the battle against COVID-19. In this review, updated clinical effects and potential mechanisms of TCM, presented in newly recognized three distinct phases of the disease, are summarized and discussed. By integrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
135
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 249 publications
(365 reference statements)
1
135
0
2
Order By: Relevance
“…To combat infection by COVID-19, extracts from different medicinal plants (including from Artemisia spp.) have been tested against COVID-19 ( Bahrami et al, 2020 ; Bailly and Vergoten, 2020 ; Huang et al, 2020 ; Kapepula et al, 2020 ; Koshak and Koshak, 2020 ; Mani et al, 2020 ; Verma et al, 2020 ; Williamson and Kerimi, 2020 ; Belhassan et al, 2021 ; Hassanipour et al, 2021 ; Javed et al, 2021 ; Lyu et al, 2021 ; Nazrul Islam et al, 2021 ; Song et al, 2021 ).…”
Section: Artemisinins: Potentials In Combating Covid-19 and Other Hum...mentioning
confidence: 99%
“…To combat infection by COVID-19, extracts from different medicinal plants (including from Artemisia spp.) have been tested against COVID-19 ( Bahrami et al, 2020 ; Bailly and Vergoten, 2020 ; Huang et al, 2020 ; Kapepula et al, 2020 ; Koshak and Koshak, 2020 ; Mani et al, 2020 ; Verma et al, 2020 ; Williamson and Kerimi, 2020 ; Belhassan et al, 2021 ; Hassanipour et al, 2021 ; Javed et al, 2021 ; Lyu et al, 2021 ; Nazrul Islam et al, 2021 ; Song et al, 2021 ).…”
Section: Artemisinins: Potentials In Combating Covid-19 and Other Hum...mentioning
confidence: 99%
“…Meanwhile, these TCMs achieved good results in fighting against SARS-CoV infection in 2003. Moreover, in the 74187 confirmed cases of SARS-CoV-2 infection reported in China, the effective rate of receiving TCM treatment was more than 90%, and its main effect was to significantly improve and shorten the course of disease, delay disease progression, and reduce mortality ( 248 ). At the same time, traditional Chinese medicine has also been confirmed to have a low incidence of adverse reactions and often self-healing in the treatment of COVID-19 patients ( 249 ).…”
Section: Potential Therapeutic Strategies and Promising Anti-sars-cov...mentioning
confidence: 99%
“…In addition to directly blocking the replication and invasion of SARS-CoV-2, several active ingredients in Qingfei Baidu Decoction, Xuanfei Baidu Decoction, Huashi Baidu Decoction, Jinhua Qinggan Granules, Huoxiang Zhengqi Capsules, Lianhua Qingwen Capsules, Shufeng Jiedu Capsules, Xuebi Jing injection, Reduning injection, Tanreqing injection and Shenmai injection have been proven to not only reduce inflammation and inflammatory storms but also regulate cytokines and immune dysfunction by regulating multiple signal pathway abnormalities in patients, thus alleviating SARS-CoV-2-induced COVID-19 ( 253 ). In the process of studying the damage of SARS-CoV-2 to organ function, clinical analysis found that Qingfei Paidu Decoction, Jinhua Qinggan Granules, Lianhua Qingwen Capsules, and Shufeng Jiedu Capsules may play a protective role in organ damage through the effects of expectorant, anti-inflammatory, antioxidant, and antifibrosis ( 248 , 252 ).…”
Section: Potential Therapeutic Strategies and Promising Anti-sars-cov...mentioning
confidence: 99%
“…Many herbal prescriptions showed excellent efficacy, for example, Lianhua Qingwen capsule [ 18 , 19 ], Qingfei Paidu decoction [ 20 , 21 ], Xuebijing injection [ 22 ] and Maxing Shigan decoction [ 23 , 24 ]. These formulae play multiple roles through multi-targets and multi-pathways, including mostly antivirus, anti-inflammation and immunoregulation [ 25 , 26 ]. However, the valuable Chinese medicines (CMs) pairs beneficial to COVID-19 and their pharmacological mechanisms remain to be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%